Perceptions and Practices towards Anthrax in Selected Agricultural Communities in Arua District, Uganda - Joseph M. Kungu; Peninah Nsamba; Alfred Wejuli; John D. Kabasa; William Bazeyo (Journal of Tropical Medicine)
Background. Anthrax is globally recognized as an important public health and economic challenge in many agricultural communities. A cross-sectional study was conducted in three subcounties in Arua district to assess the community’s awareness, cultural norm, and practices regarding anthrax. This followed a report of active cases of human cutaneous anthrax in the district. Methods. The study was conducted in subcounties of Pawor, Rigbo, and Rhino Camp, Arua district, using focus group discussion. Results. The affected communities had limited knowledge about anthrax, especially its clinical manifestation and modes of transmission both in humans and animals. The community also had no knowledge of the anthrax vaccine or treatment and where they can be accessed from. Poor practices associated with anthrax outbreaks included poor disposal of carcasses and ruminal wastes, occupational hazards (butchers, slaughter men, and herdsmen), consumption of meat from infected animals, communal herding, and cultural norms encouraging consumption of dead animals. Conclusion. This study shows that there is a knowledge gap about anthrax among the people in the affected communities. Key drivers for the anthrax outbreak such as poor cultural beliefs and practices and wildlife-livestock-human interactions were observed in all the three subcounties studied. All these findings could imply a high risk of outbreak of anthrax in Arua and Ugandan agricultural communities where the public health programs are less standardized and less effective.